Antinociceptive and anti-inflammatory effect of a standardized fraction of Oenothera rosea L'Hér. ex Aiton and its possible mechanism of action in mice - Rodrigo Vargas-Ruiz; Jose Eduardo Roa-Coria; Arturo Mora-Olivo; Alejandro Zamilpa; Maribel Lucila Herrera-Ruiz; Rosa Issel Acosta-Gonzalez; Rosa Mariana Montiel-Ruiz (Mashhad University of Medical Sciences, 2022)
Objective: This study was conducted to investigate the antinociceptive and anti-inflammatory effect of ethyl acetate fraction of Oenothera rosea (EAOr) and the mechanism involved, in mice.Materials and Methods: The antinociceptive activity was tested using chemical- and heat-induced nociception models. The anti-inflammatory activity was tested using carrageenan-induced edema and inflammatory cytokines were measured.Results: EAOr reduced the licking time on the second phase of the formalin test (100 and 177 mg/kg). The antinociception of EAOr was prevented by L-NAME (10 mg/kg), 1H-[1, 2, 4]-oxadiazolo [4, 3-a]-quinoxalin-1-one (ODQ, 0.1 mg/kg), glibenclamide (10 mg/kg) and bicuculline (1 mg/kg), but not by naloxone (2 mg/kg). Also, EAOr decreased licking time in capsaicin induced-nociception. EAOr did not have effect on withdrawal latency in tail-flick test. Carrageenan-induced paw edema was reduced by EAOr, and TNF-α and IL-1β levels were reduced in mice treated with EAOr by 72.2 and 32.8%, respectively. Furthermore, EAOr did not present side effects as sedation nor gastric injury. Chemical analysis of this fraction showed the presence of glycosylated quercetin derivatives such as quercetin glucoside and quercetin rhamnoside in a 2.5% concentration.Conclusion: This study demonstrates antinociceptive and anti-inflammatory effect of an organic fraction of O. rosea and its possible interaction with the NO-cGMP-K+ channels and GABAergic system and thus, it could be considered a therapeutic alternative.